(untitled) (International Journal of Engineering and Computer Science, 2016)
Green IT is an effective approach to the practice and procedures of using computer resources in an environment friendly way while maintaining overall computing performance. The paper is going to describe the hazards causes by the computer and about the safety measures by which we can save our environment from those. Green IT is a well balanced and sustainable approach towards the achievement of a healthier, greener and safer environment. With Green IT we can build an energy efficient computer system and the other hand we can also reduce energy consumption by using IT. Green IT is comprised of initiatives and strategies that reduce the environmental footprints of technology. Green IT initiative also produces cost savings in energy use, purchase, management and support in addition to environmental benefits. Proper implementations of Green Computing or Green IT an individual and or a organization can reduce almost fifty percent of energy consumption per year, by which a organization not only save the energy but also produce more products with lower cost.